Reliability-Based Design of Reinforced Concrete Beams for Simultaneous Bending, Shear, and Torsion Loadings - Faezeh Jafari; Jalal Akbari (Fracture and Structural Integrity)
Designing structural members is targeted in resisting against the loads such that the safety of considered structure is maintained regarding different conditions of loading. The method existing in ACI guideline is considered using load and resistance factors regardless of random nature of design parameters.  Existing uncertainties in design parameters such as load and resistance have caused changes in safety of structure and the use of constant coefficients in different states of loading has often caused design unsafely. The present research has discussed the design of all the probabilities for reinforced concrete beams subjected to bending, shear and torsion stresses. For this, analytical relations of limit state have been developed to combine different stresses. Monte Carlo method is the method used to calculate safety measures, in which safety surface of American Concrete Institute (ACI) and different limit states have been calculated for three different sections (T-shape, rectangular shape and L-shape). The results of paper indicate that the safety index is considered in the range of 3 to 4 at different limit states. Load and resistance coefficients have been calculated in different safety indices and influence of load and resistance coefficients on American Concrete Institute (ACI) have been examined. Using the proposed method, designer enables to take an action for design by changing the conditions governing the problems such as dimensions, load and features of the section regarding the safety of structure. Further, under use of constant coefficients with sufficient information on composition of the considered loads, the designer enables to design and ratio of load and different limit states of the considered structure. Studying influence of changes of numbers in load and resistance coefficients on American Concrete Institute (ACI) has been mentioned as the major objective of the present research, indicating that resistance coefficient has more significantly influence on American Concrete Institute (ACI) in different loading compositions.